EVC-EVC2 complex stability and ciliary targeting are regulated by modification with ubiquitin and SUMO - Barbeito, Pablo; Martin-Morales, Raquel; Palencia-Campos, Adrian; Cerrolaza, Juan; Rivas-Santos, Celia; Gallego-Colastra, Leticia; Caparros-Martin, Jose Antonio; Martin-Bravo, Carolina; Martin-Hurtado, Ana; Sánchez-Bellver, Laura; Marfany, Gemma; Ruiz-Perez, Victor L.; et al. (Frontiers in Cell and Developmental Biology, 2023)
Ellis van Creveld syndrome and Weyers acrofacial dysostosis are two rare genetic diseases affecting skeletal development. They are both ciliopathies, as they are due to malfunction of primary cilia, microtubule-based plasma membrane protrusions that function as cellular antennae and are required for Hedgehog signaling, a key pathway during skeletal morphogenesis. These ciliopathies are caused by mutations affecting the EVC-EVC2 complex, a transmembrane protein heterodimer that regulates Hedgehog signaling from inside primary cilia. Despite the importance of this complex, the mechanisms underlying its stability, targeting and function are poorly understood. To address this, we characterized the endogenous EVC protein interactome in control and Evc-null cells. This proteomic screen confirmed EVC’s main known interactors (EVC2, IQCE, EFCAB7), while revealing new ones, including USP7, a deubiquitinating enzyme involved in Hedgehog signaling. We therefore looked at EVC-EVC2 complex ubiquitination. Such ubiquitination exists but is independent of USP7 (and of USP48, also involved in Hh signaling). We did find, however, that monoubiquitination of EVC-EVC2 cytosolic tails greatly reduces their protein levels. On the other hand, modification of EVC-EVC2 cytosolic tails with the small ubiquitin-related modifier SUMO3 has a different effect, enhancing complex accumulation at the EvC zone, immediately distal to the ciliary transition zone, possibly via increased binding to the EFCAB7-IQCE complex. Lastly, we find that EvC zone targeting of EVC-EVC2 depends on two separate EFCAB7-binding motifs within EVC2’s Weyers-deleted peptide. Only one of these motifs had been characterized previously, so we have mapped the second herein. Altogether, our data shed light on EVC-EVC2 complex regulatory mechanisms, with implications for ciliopathies.